2006
DOI: 10.1002/ijc.22052
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survival is dependent on season of diagnosis and sunlight exposure

Abstract: Sunlight is essential for the production of vitamin D in the body. Evidence exists to suggest that vitamin D metabolites may have a role in tumor growth suppression. In this large study, involving over a million cancer patients from the United Kingdom, we have analyzed the role of season of diagnosis and sunlight exposure in cancer survival for cancers of the breast, colorectum, lung, prostate and at all sites combined. We used population-based data from the Thames Cancer Registry to analyze cancer survival in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 40 publications
9
90
1
2
Order By: Relevance
“…Several epidemiological studies have demonstrated an association between the diagnosed season of cancer and subsequent survival, with cancer patients diagnosed in the summer and autumn months having better survival in most of these studies (Robsahm et al, 2004;Lim et al, 2006;Porojnicu et al, 2008). However, few studies have examined the association between diagnosed season and the prognosis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiological studies have demonstrated an association between the diagnosed season of cancer and subsequent survival, with cancer patients diagnosed in the summer and autumn months having better survival in most of these studies (Robsahm et al, 2004;Lim et al, 2006;Porojnicu et al, 2008). However, few studies have examined the association between diagnosed season and the prognosis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…During winter months, the endogenous synthesis of vitamin D3 and the total 25-hydroxyvitamin D level in serum are up to one half of the corresponding states during the summer and autumn months (Poskitt et al, 1979;Vik et al, 1980). Several studies indicated that the prognosis of many cancers such as lung -prostate-, breast-, colon cancer and Hodgkin lymphoma is related to the season of diagnosis (Lim et al, 2006;Porojnicu & Lagunova et al, 2007;Porojnicu et al, 2008;Mutlu et al, 2013;Oguz et al, 2013). Patients with breast cancer and colon cancer diagnosed in the summer and autumn have better survival comparing to those diagnosed in winter (Moan et al, 2005;Porojnicu & Lagunova et al, 2007), although opposite results were reported by Mutlu et al (2013).…”
Section: Recurrence Season Impacts the Survival Of Epithelial Ovarianmentioning
confidence: 99%
“…However, in our study, for 1 and 2 years survival rates, a significant correlation with seasonality was not detected for advanced NSCLC cases. Lim et al (2006) analyzed the effect of sunlight exposure and season of diagnosis and sunlight exposure on more than a total of a million colorectal, lung, breast and prostate cancer patients. They have found that, patients diagnosed in summer and autumn showed prolonged survivals than those diagnosed in winter, especially in lung and breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of season in which the cancers were diagnosed, on the outcomes of patients has been studied in several large epidemiologic studies (Lim et al, 2006;Porojnicu et al, 2008;Roychoudhuri et al, 2009;La Par et al, 2011). In most of these studies it has been shown that winter months are associated with poorer prognosis that may be explained through the variations in the cutaneous production of vitamin D3.…”
Section: Introductionmentioning
confidence: 99%
“…In most of these studies it has been shown that winter months are associated with poorer prognosis that may be explained through the variations in the cutaneous production of vitamin D3 (Lim et al, 2006;Roychoudhuri et al, 2009;La Par et al, 2011).…”
Section: Discussionmentioning
confidence: 99%